High-K, I-type Tonian post-collisional magmatism in the South Delhi Terrane, NW India: Petrogenetic and tectonic implications - Manisha; Parampreet Kaur; Naveen Chaudhri (Geosystems and Geoenvironment)
The limited whole-rock geochemical data of the granitoids exposed in the southern domain of the South Delhi Terrane, Aravalli orogen, northwestern India characterised these rocks as subduction-related continental arc I-type granites. The new comprehensive mineralogical and geochemical data of these Tonian (975–965 Ma) granitoids, particularly those exposed around the Bekariya region, reveal that they are not continental arc I-type granites. These granitoids are rather high-K, I-type, weakly peraluminous to metaluminous, magnesian to ferroan, calc-alkalic to calcic and emplaced in a post-collisional extension regime. They comprise predominantly high-temperature (764–845°C) granitoids, along with a subordinate volume of low-temperature (669–776°C) granitoids. The nearly flat to variably inclined [(Gd/Yb)N = 1.0–4.8)] and depleted [(Gd/Yb)N = 2.8–3.0)] HREE patterns of the granitoids with notable negative (Eu/Eu* = 0.21–0.71) and insignificant (Eu/Eu* = 0.83–0.85) Eu anomalies, respectively and variable Sr/Y ratios (0.6–93.9), imply variation in the depth of their magma generation. Taken together, these data suggest that the high-temperature I-type Bekariya granitoids most likely originated from dehydration partial melting of metabasaltic-metandesitic crust that required a significant influx of heat in a post-collisional or post-orogenic setting. In contrast, the minor low-temperature I-type granitoids probably resulted from partial melting of a similar source by the infiltration of a water-rich fluid phase in a subduction-related setting. Furthermore, the study signifies that I-type granitoids are more voluminous than A-type granitoids in the South Delhi Terrane and were emplaced coevally in a post-collisional extension regime during the Tonian period.